Criminal Legislation of Ukraine on Crimes in the Field of Information Technologies - Toronchuk, Ivan; Krainii, Pavlo (Black Sea Maritime Cyber Security, 2020)
The article under studies reveals the general aspects of legal regulation of crime prevention in the field of information technology, analyzes the statistics of crimes in this area, as well as identifies the basic issues of the criminal-legal qualification of offenses in the field of applying computers, computer systems, computer and telecommunication networks